Politisasi Birokrasi Pasca Pilkada di Indonesia: Dilema Profesionalisme dan Kekuasaan - Robyan Endruw Bafadal; Zulkarnain; Lalu M. Istiqlal (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2026)
This study aims to analyze the forms, mechanisms, and impacts of bureaucratic politicization in the post-Pilkada period on the professionalism of the State Civil Apparatus (Aparatur Sipil Negara—ASN) and regional governance. The study employs a library research approach by examining books, journal articles, regulations, and previous studies relevant to the topic. Data were analyzed using a descriptive qualitative method through classification, interpretation, and synthesis of findings. The results indicate that bureaucratic politicization after Pilkada occurs through promotion, transfer, demotion, and appointment processes based on political loyalty. These practices foster patronage relationships between regional heads and bureaucrats, thereby undermining the merit system in the management of civil servants. The consequences include declining bureaucratic neutrality, weakened professionalism among public officials, deteriorating public service quality, and the increasing prevalence of patronage and nepotism within regional governments. From the perspective of the Political Control of Bureaucracy Theory, these findings suggest that excessive political control may evolve into political domination that threatens bureaucratic independence. Therefore, strengthening the merit system, enhancing oversight of ASN neutrality, and limiting political intervention are essential prerequisites for establishing a professional, accountable, and effective bureaucracy.